How to make a knowledge-sharing group: a group social capital perspective. Issue 3 (4th April 2016) - Wu, Wei-Li; Lee, Yi-Chih
Abstract : Purpose: – Although the work group is the main context for knowledge exchange and combination in today's organizations, few knowledge-sharing studies have been conducted at the group level. The purpose of this paper is to apply the concept of group social capital to determine how to promote knowledge sharing at the group level. The authors divided group social capital into two segments, conduits and resources, and argue that different group social capital conduits (i.e. work design in this study) lead to varied resources, which subsequently influence group knowledge sharing. Design/methodology/approach: – In this study, group social capital conduits included social interaction and task interdependence, and group social capital resources included group trust and a supportive climate for knowledge sharing. The authors conducted a survey on work groups in the high-tech industry using a sample of 86 work groups. Findings: – The results indicated that social interaction in a work group was positively related to group trust and that task interdependence was positively related to group trust and a supportive climate for knowledge sharing. Furthermore, group trust and a supportive climate for knowledge sharing were both found to have an influence on knowledge sharing. Originality/value: – Applying the concept of group social capital, this paper is the first research to discuss how group social capital conduits and resources influence knowledge sharing. The results of this study lead us to a better understand the relationship between group social capital and knowledge sharing.